Ecological Sensitivity Assessment of Xinyi City in Guangdong Province Based on GIS and AHP - Ye, Xiaodong; Wang, Ruei-Yuan (International Journal of Environment, Agriculture and Biotechnology, 2024)
Ecological sensitivity analysis is an important basis for urban planning and layout. This article selects six ecological evaluation factors, including altitude, slope, aspect, water environment, vegetation NDVI, and land use, to construct an ecological sensitivity evaluation system for Xinyi City. Using the spatial analysis techniques of GIS and the Analytic Hierarchy Process (AHP), a comprehensive evaluation was conducted on six ecological evaluation factors. Meanwhile, the natural breakpoint method was used to divide the results into five levels: extremely sensitive area, high sensitive area, medium sensitive area, low sensitive area, and non-sensitive area. The results indicate that the ecological sensitivity of Xinyi City is generally high, and land use type, vegetation coverage, and water environment are the main factors affecting ecological sensitivity. The five sensitive areas, from non-sensitive to extremely sensitive, account for 0.71%, 18.44%, 38.88%, 33.01%, and 8.96% of the total area of the city, respectively. The highly sensitive areas of Xinyi City are distributed in the northeast, while the non-sensitive areas are distributed in the southwest. The comprehensive evaluation of ecological sensitivity and spatial layout in this article can provide a basis for land use construction planning and ecological environment protection in Xinyi City.